2023
DOI: 10.3390/polym15122600
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sorption and Degradation of Polymer Filaments Used in 3D Printing

Abstract: Experimental research of the moisture sorption process of 12 typical filaments used for FFF was performed in atmospheres with a relative humidity from 16 to 97% at room temperature. Materials with high moisture sorption capacity were revealed. Fick’s diffusion model was applied to all tested materials, and a set of sorption parameters was found. The solution of Fick’s second equation for the two-dimensional cylinder was obtained in series form. Moisture sorption isotherms were obtained and classified. Moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The moisture content of CF/ABS specimens increased and approached saturation levels at the end of the testing period. Aniskevich et al [ 45 ] reported similar moisture uptake behavior in 3D-printed ABS polymers.…”
Section: Resultsmentioning
confidence: 83%
“…The moisture content of CF/ABS specimens increased and approached saturation levels at the end of the testing period. Aniskevich et al [ 45 ] reported similar moisture uptake behavior in 3D-printed ABS polymers.…”
Section: Resultsmentioning
confidence: 83%
“…Moreover, the degradation of tensile properties due to moisture absorption was studied for twelve different filaments, including PEI and PEKK [3]. According to the results obtained, both materials were classified as having a moderate (5-9%) sensitivity to water by their reduction in mechanical properties, while the maximal moisture sorption capacity and swelling coefficient of PEI were almost twice as high as for PEKK.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Additive manufacturing has gained widespread adoption across various sectors due to several compelling motivations, such as design flexibility, reduced material waste, rapid prototyping, customization, supply chain simplification, tooling and assembly reduction, and environmental benefits [1][2][3]. These advantages drive the use of additive manufacturing across various industries, e.g., aerospace, automotive, healthcare, defence, and military, promising improved efficiency, reduced costs, and innovative product development [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…PLA plastic is known to be susceptible to moisture absorption, which can result in hydrolytic degradation during the filament extrusion process. This degradation may cause the breakdown of polymeric chains and decrease the material elongation [77][78][79]. However, the same moisture content acts as a plasticiser, making the material softer and more ductile [79].…”
Section: Tensile Behaviourmentioning
confidence: 99%